A One Health approach to prevention, treatment, and control of campylobacteriosis - Schiaffino F. (2019)
Purpose of review: To review recent findings regarding the control and treatment of campylobacteriosis. Recent findings: The application of improved diagnostics has led to an upward shift in the attributable burden of Campylobacter infections, in both the United States and Europe as well as in resource-poor settings. Increased focus has brought a fundamental feature of campylobacteriosis - the ability to cause relapsing disease back into focus, and expanding data on antimicrobial resistance has lead from a switch in first-line therapy for severe diarrhea from quinolones to azithromycin in most contexts, even as evidence of expanding macrolide resistance emerges. Summary: Campylobacter spp. infection is a common infection worldwide. Antibiotic-resistant Campylobacter spp. has become an emerging threat with the increase in industrial poultry production, as well as the broad use of antibiotics in both animals and humans. Copyright © 2019 Wolters Kluwer Health, Inc. All rights reserved.